The Role of Internal Control in Reducing the Risk of Room Reservation Fraud at Adi Rama Beach Hotel - UTAMA, I Gusti Ngurah Indra Pracita; DARMAWAN, I Made Endi; JULIARTA, I Wayan; SUARDANA, Dewa Gede (PT. Keberlanjutan Strategis Indonesia, 2025)
Purpose:In recent times, Adirama Beach Hotel has also experienced difficulties in maintaining the reliability, openness, and security of data related to the room reservation process that occurs at this hotel. It shows that the current system is vulnerable to fraudulent practices that are detrimental to the hotel and guests. This study aims to analyze whether the internal control of the accounting information system implemented by Adirama Beach Hotel can support all managerial activities in making more effective and efficient decisions.Methodology:The research method used in this study is descriptive qualitative, with a focus on explaining how the implementation of good internal control can overcome fraud in room reservation management.Findings:Based on the results of the internal audit conducted, there are several weaknesses in the control system implemented in this hotel, such as the lack of adequate supervision of the reservation process, as well as low audit frequency. These weaknesses allow fraud to occur, which is detrimental to the company. Therefore, to overcome this problem, it is necessary to improve supervision, regular training for employees, and the implementation of more advanced technology to support a more effective internal control system.Implication:With these improvements, it is expected that Adirama Beach Hotel can minimize the risk of fraud, improve accuracy in recording reservation data, and increase transparency and security of existing information. Ultimately, these improvements will support better decision-making in hotel management and help increase the company's overall profits.